Relative abundance and autecology of three piscivorous fishes in lakes of the upper basin of Salado River (Buenos Aires Province, Argentina) - Barla, María Julia (2003)
The Salado River is an important watercourse in northern Pampean region of Argentina which includes several lakes in the upper part of its basin. This upper part shows lesser fish species richness than the lower section of the river. In this paper, an analysis of community structure of secondary and tertiary consumers and its autecology are presented. Among the 14 fish species recorded, 3 were mainly or totally piscivorous as adults. They constituted 11.4% of the numeric abundance and 10.8% of the biomass. Their numeric abundance was 89% (Oligosarcus jenynsii), 11% (Rhamdia sapo), and 0.5% (Hoplias malabaricus malabaricus), and their relative biomass was 61%, 33%, and 6%, respectively. Length/weight ratio, condition factor, and cephalic index indicate that the three populations presented normal development. Stomachs were classified according to the degree of repletion. Differences in repletion were attributable to the feeding behaviour of the different species. The relative abundance differed from the one observed in other environments within the same basin. This variation could be the result of interspecific competition or of differences in resource availability.